Analysis Of Mental Health Communication Messages In The Film “Kukira Kau Rumah” - Elta Enjelita; Dedet Erawati (Ann Publisher, 2026)
Background. Film as a mass communication medium plays a strategic role in conveying mental health messages to the public. One Indonesian film that raises this issue is Kukira Kau Rumah by Umay Shahab, which represents the experiences of individuals with bipolar disorder and depression through narrative, dialogue, and visual symbols. Aims. This study aims to analyze how mental health communication messages are constructed and conveyed in the film Kukira Kau Rumah, and how these messages are interpreted by the audience. Methods. This study uses a qualitative approach with content analysis, reinforced by audience reception analysis using Stuart Hall's encoding–decoding theory, Entman's framing theory, and Smith's communication stigma theory as supporting theories. Data were obtained through in-depth observation of the film and semi-structured interviews with three informants aged 20 to 23 who had watched the film. Result. The results show that the film Kukira Kau Rumah effectively conveys mental health communication messages through its depiction of emotional instability, bipolar depression, medical diagnosis, family pressure, and the importance of social support. Conclusion. The messages conveyed by the film are largely accepted by the audience, thereby building empathy, increasing understanding, and reducing stigma towards people with mental disorders. Implementation. This film can be viewed as an educational, humanistic, and relevant medium of health communication for the community, especially the younger generation.